Correlation of climate factors and the number of SARS-CoV-2 cases at Semarang, Central Java - Maulana, Mochamad Rizal; Sofyanita, Eko Naning; Swastya Putri, Adita Puspitasari (International Journal of Public Health Science (IJPHS), 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new type of coronavirus that has symptoms of acute respiratory distress in general. In more severe, it can cause kidney failure, pneumonia, and death. Environmental conditions that cannot be anticipated, such as climate factors, can have an impact on the transmission and survival of viruses, including the severe acute respiratory syndrome (SARS) viruses, which are responsible for the emergence of respiratory diseases. This research is a quantitative study using an ecological approach with secondary data from the Meteorology, Climatology, and Geophysics Agency (temperature, humidity, and precipitation), and SARS-CoV-2 cases were sourced from the Semarang City COVID-19 Task Force in 2021 were univariate and bivariate analyzing. The highest temperature average occurs in October (29.8 ⁰C), the humidity average occurs in February (91.4%), and the average precipitation occurs in February (1,130 mm). Analysis of the correlation found that there was a correlation between the SARS-CoV-2 cases with humidity (p=0.000; r=-0.245) and temperature (p=0.016; r=-0.127), but there was no correlation between precipitation (p=0.403; r=-0.044). Analysis of the influence of meteorological elements related to temperature, humidity, and precipitation on the incidence of COVID-19 in Semarang City in 2021, it can be concluded that there is correlation between temperature and humidity on COVID-19 cases except for precipitation.